Composite Models for Short Term Forecasting for Natural Rubber Prices - Shamsudin, Mad Nasir; Mohd Arshad, Fatimah (1990)
The economet1ic technique and Box-jenhins univariate method have been applied in forecasting natural rubber prices. This study developed a short term forecasting model known as the composite model, by combining the econometric and univariate models. The results indicate that the composite model produces more efficient forecasts than the econometric and univariate models.